2018
DOI: 10.1016/j.bbrc.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 hyperactivation reduces neuropathology and behavioral deficits in zQ175 knock-in mouse model of Huntington's disease

Abstract: Mitochondrial dysfunction manifests in the pathogenesis of Huntington’s disease (HD), a fatal and inherited neurodegenerative disease. Dynamin-related protein 1 (Drp1) is the primary component of mitochondrial fission and becomes hyperactivated in various models of HD. We previously reported that inhibition of Drp1 hyperactivation by P110, a rationally designed peptide inhibitor of Drp1-Fis1 interaction, is protective in the HD R6/2 mouse model, which expresses a fragment of mutant Huntingtin (mHtt). In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Many of the studies currently published that utilize these compounds are in the context of targeting ischemia-reperfusion injury, typically with significant benefits in mitochondrial morphology and function both in vitro and in vivo ( 277 , 282 285 , 290 , 388 ). There have also been studies examining the use of p110 and thus the proposed disruption of the Fis1-Drp1 interaction in models of sepsis related complications such as cardiomyopathy and encephalopathy ( 389 ), as well as neurological diseases including Huntington’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease; of which, these studies found significant improvement in pathogenesis and downstream effects of the diseases ( 91 , 354 , 390 392 ). These improvements are determined by criteria such as inhibition of excess mitochondrial fission, decreased reactive oxygen species production, improved mitochondrial membrane potential, and decreased apoptosis.…”
Section: Fis1 In Therapeutic Advancements and Drug Discoverymentioning
confidence: 99%
“…Many of the studies currently published that utilize these compounds are in the context of targeting ischemia-reperfusion injury, typically with significant benefits in mitochondrial morphology and function both in vitro and in vivo ( 277 , 282 285 , 290 , 388 ). There have also been studies examining the use of p110 and thus the proposed disruption of the Fis1-Drp1 interaction in models of sepsis related complications such as cardiomyopathy and encephalopathy ( 389 ), as well as neurological diseases including Huntington’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease; of which, these studies found significant improvement in pathogenesis and downstream effects of the diseases ( 91 , 354 , 390 392 ). These improvements are determined by criteria such as inhibition of excess mitochondrial fission, decreased reactive oxygen species production, improved mitochondrial membrane potential, and decreased apoptosis.…”
Section: Fis1 In Therapeutic Advancements and Drug Discoverymentioning
confidence: 99%
“…Thus, mHTT‐induced mitochondrial fission may lead to neuronal dysfunction and toxicity in HD patient brains. This hypothesis is supported by investigations in zQ175 HD mice, which showed that inhibition of DRP1 hyperactivity with a peptide reduces behavioural deficits (Zhao et al ). An abnormal interaction between mHTT and DRP1 was also detected in postmortem brains of HD patients (Shirendeb et al ).…”
Section: Mitochondrial Fission and Mitophagymentioning
confidence: 74%
“…This pathologic feature is replicated in R6/1 and R6/2 mouse models through an increase in the reaction to stress and a prolonged corticosterone responses [77,78]. An increase in anxiety-like behavior was also reported in BACHD mice in early disease [59] and at approximately 8 months in zQ175 mice [79]. Whether the reduced descending rod descent time, narrow beam cross time, and initial hyperactivity detected in female N171-82Q are influenced by an altered stress response is unknown.…”
Section: Discussionmentioning
confidence: 95%